The Antecedents of Culinary Business Performance in COVID-19 Pandemic (A Conceptual Paper) - Aziz, Ahmad Ghaffar; Wardana, Peicha Pangestu; Hidayat, Desman (Journal of Business, Management, and Social Studies, 2021)
Culinary business has been an important part of Indonesia’s Micro and Small Enterprises (MSEs). Currently, this industry has been affected by COVID-19 pandemic. This study aims to show how innovation capability mediates the relationship between entrepreneurial orientation and market orientation towards culinary business performance in Jakarta, Indonesia. This study creates a conceptual model based on the literature review of antecedents of culinary business performance. This paper shows the important concept of entrepreneurial orientation and market orientation towards business performance with innovation capability as the mediating variable. The novelty of this study is in the importance of innovation capability for helping culinary business in Jakarta to survive the COVID-19 pandemic.